As duas faces da morte : da impessoalidade de-cadente à de-cisão antecipadora. Uma reflexão a partir do pensamento de Martin Heidegger - Barcellos, Igor Awad (2015)
Martin Heidegger, considered one of greatest philosophers of contemporaneity, has as the fundamental question of his thought the question about Being. These theme pervades his work as a whole, since his first book, Being and time, originally published in 1927, until the last phase of his thought. From the fundamental ontology, it means, the question about the meaning of being in general, Heidegger thinks a lot of phenomena, and, among them, death. Death appears decisively in Being and time in the moment that Heidegger has the necessity to think Dasein´s being as a whole, it means, to the beginning until the end. Dasein´s end is death, so this theme has dignity of being considered. How should we think the phenomenon of death? Heidegger offer us the path in Being and time: from impropriety to propriety. In this way, we started our investigation: demonstrating the limitations of improper comprehension about death as investigating what Dasein´s impropriety is; later, we considerate death in a proper sense, in other words being-to-death, introducing fundamental concepts of Heidegger´s philosophy, as anguish, comprehension, humor, speech, until we find the phenomena of anticipatory decision. This is the privileged opening of Dasein in which this being take up his own death and unravel himself in totality.